T-cell phenotypes in chronic rhinosinusitis with nasal polyps in Japanese patients. Issue 1 (December 2015) - Baba, Shintaro; Kagoya, Ryoji; Kondo, Kenji; Suzukawa, Maho; Ohta, Ken; Yamasoba, Tatsuya
Abstract Background Chronic rhinosinusitis with nasal polyps is characterized by local inflammation and is categorized into two subtypes in Japan: eosinophilic chronic rhinosinusitis, and non-eosinophilic chronic rhinosinusitis. The objective of this study was to investigate the expression of key transcription factors for Treg and Th1/Th2/Th17 cells, in relation to the mRNA expression of representative cytokines in these two subtypes of chronic rhinosinusitis with nasal polyps. Methods The expression of forkhead box P3 (FOXP3), T-box transcription factor (T-bet), GATA3, retinoid acid-related orphan receptor C (RORc), the suppressive cytokines TGF-β1 and IL-10, and Th1/Th2/Th17 cytokines (IFN-γ, IL-4, IL-5, IL-13, IL-17) were analyzed by means of RT-PCR in eosinophilic polyps. Eosinophilic polyps were defined as having an eosinophil count of more than 50 per microscopic field (×400 magnification) using five fields located in the subepithelial area of the polyps, while the non-eosinophilic polyps and controls did not fulfill this criteria. The numbers of T cells, CD4+ T cells, CD8+ T cells and Treg were histologically counted using sections that were immunostained for CD3, CD4, CD8, and FOXP3, respectively. Results In eosinophilic polyps, we observed significantly fewer CD4+ T cells and CD8+ T cells, and lower GATA3, RORc and IL-10 mRNA expression, but a significantly higher IL-5, and IL-13 mRNA expression compared with controls, whereas FOXP3 and T-bet mRNA expression were not significantly different compared with controls. In non-eosinophilic polyps, FOXP3, IL-10, IL-17A, TGFβ1 and IFNγ mRNA expression was significantly higher compared with controls, whereas IL-4, 5 and 13 expression was not significantly different from controls. Conclusion We showed a reduction of GATA3 and RORc mRNA, low Treg-related cytokines and elevated Th2 cytokine levels in eosinophilic chronic rhinosinusitis, whereas we demonstrated the upregulation of Treg cells and increases of Th1 and Th17 cytokines in non-eosinophilic chronic rhinosinusitis in the Japanese population. The different mRNA expression profiles of Treg and Th1/Th2/Th17 signature transcription factors and cytokines between eosinophilic chronic rhinosinusitis and non-eosinophilic chronic rhinosinusitis suggests heterogeneity in the pathogenesis of chronic rhinosinusitis with nasal polyps.